Highly Efficient Multi‐Resonance Thermally Activated Delayed Fluorescence Material with a Narrow Full Width at Half‐Maximum of 0.14 eV. Issue 4 (4th December 2021) - Liu, Futong; Cheng, Zhuang; Wan, Liang; Feng, Zijun; Liu, Hui; Jin, Haixu; Gao, Lei; Lu, Ping; Yang, Wensheng
Abstract: Multi‐resonance thermally activated delayed fluorescence (MR‐TADF) material, which possesses the ability to achieve narrowband emission in organic light‐emitting diodes (OLEDs), is of significant importance for wide color gamut and high‐resolution display applications. To date, MR‐TADF material with narrow full width at half‐maximum (FWHM) below 0.14 eV still remains a great challenge. Herein, through peripheral protection of MR framework by phenyl derivatives, four efficient narrowband MR‐TADF emitters are successfully designed and synthesized. The introduction of peripheral phenyl‐based moieties via a single bond significantly suppresses the high‐frequency stretching vibrations and reduces the reorganization energies, accordingly deriving the resulting molecules with small FWMH values around 20 nm/0.11 eV and fast radiative decay rates exceeding 10 8 s −1 . The corresponding green OLED based on TPh‐BN realizes excellent performance with the maximum external quantum efficiency (EQE) up to 28.9% without utilizing any sensitizing host and a relatively narrow FWHM of 0.14 eV (28 nm), which is smaller than the reported green MR‐TADF molecules in current literatures. Especially, the devices show significantly reduced efficiency roll‐off and relatively long operational lifetimes among the sensitizer‐free MR‐TADF devices. These results clearly indicate the promise of this design strategy for highly efficient OLEDs with ultra‐high color purity. Abstract : The introduction of peripheral phenyl substituents can significantly suppress the high‐frequency stretching vibrations and reduce the reorganization energies to achieve narrower bandwidth emission. The corresponding device exhibits high external quantum efficiency up to 28.9% and small full width at half maximum of only 0.14 eV, which is among the best values of the reported boron‐nitrogen‐containing materials.